2010
DOI: 10.3399/bjgp10x532422
|View full text |Cite
|
Sign up to set email alerts
|

Validity of British Thoracic Society guidance (the CRB-65 rule) for predicting the severity of pneumonia in general practice: systematic review and meta-analysis

Abstract: The CRB-65 score is a clinical prediction rule that grades the severity of community-acquired pneumonia in terms of 30-day mortality. AimThe study sought to validate CRB-65 and assess its clinical value in community and hospital settings. Design of studySystematic review and meta-analysis of validation studies of CRB-65. Medline (1966 to June 2009), Embase (1988 to November 2008, British Nursing Index (BNI) and PsychINFO were searched, using a diagnostic accuracy search filter combined with subject-specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 38 publications
0
67
0
10
Order By: Relevance
“…Moreover, there is no consensus about risk thresholds, and different groups consider different thresholds to be acceptable. 10,25 …”
Section: What Is the Acceptable Risk Of Adverse Events In A Dischargementioning
confidence: 99%
“…Moreover, there is no consensus about risk thresholds, and different groups consider different thresholds to be acceptable. 10,25 …”
Section: What Is the Acceptable Risk Of Adverse Events In A Dischargementioning
confidence: 99%
“…There have been three recent systematic reviews of evidence for using severity assessment rules in the management of CAP. [10][11][12] Two of these excluded patients who had not had a chest x-ray. 10,11 This limited the applicability of the findings as an x-ray is not performed for most patients with LRTI managed in the community.…”
Section: Introductionmentioning
confidence: 99%
“…The third review compared the use of the CRB-65 to predict 30-day mortality in hospital and community settings, and found that the rule over-predicted the probability of mortality in community settings. 12 However, while studies have evaluated the use of CRB-65 in outpatient clinics, emergency departments, and private specialist clinics, [13][14][15][16] only one study has evaluated its use in primary care, and this study was limited to older patients (aged >65 years) with an empirical diagnosis of pneumonia. 17 No study has yet assessed the extent to which primary care clinicians routinely assess the features that make up the CRB-65 score, the value of the CRB-65 in all adults presenting with LRTI in primary care, or whether the tool can be used to predict more severe or prolonged illness in the community.…”
Section: Introductionmentioning
confidence: 99%
“…CURB-65 has fewer variables than the Pneumonia Severity Index (PSI), which requires 20 separate patient characteristics and does not require obtaining an arterial blood gas, yet has demonstrated similar accuracy in predicting 30-day mortality in studies of patients who have been hospitalized. [11][12][13][18][19][20][21][22][23][24][25] Patients who were kept in the hospital under observation status were included among patients admitted to the hospital. CURB-65 scores were calculated based on the established severity scoring system 19 for each adult ED pneumonia encounter, using elements from the electronic health record.…”
Section: Measurementsmentioning
confidence: 99%